Intraoperative Three-dimensional Imaging for Detection of Malreduction during Tibiofibular Syndesmosis Reconstruction—Evaluating Fibula–Tibia Positional Accuracy and Outcomes: Case Series - Adriaan L Franx; Corné Kanters; Inger B Schipper; Pieta Krijnen; Jochem M Hoogendoorn; Sander M Verhage (Journal of Foot and Ankle Surgery (Asia Pacific))
Aims and background: Distal tibiofibular syndesmosis injuries often require stabilization to prevent osteoarthritis (OA) and functional impairment. Malreduction rates up to 52% have been reported after fluoroscopy-guided fibula–tibia (fib–tib) positioning screw placement, and malreduction is associated with poor outcomes, including chronic pain, instability, and posttraumatic arthritis. Traditional two-dimensional (2D) fluoroscopy often fails to detect subtle malreductions, contributing to these suboptimal results. In contrast, intraoperative three-dimensional (3D) imaging modalities, such as computed tomography (CT) or cone-beam CT, are increasingly utilized to improve detection of malalignment during surgery. This study evaluates if intraoperative 3D imaging in syndesmotic reconstruction using fib–tib positioning screws improves detection of malreduction and assesses how often 3D imaging leads to intraoperative revision of reduction. Materials and methods: This retrospective case series includes all patients (n = 22) who underwent syndesmotic reconstruction by fib–tib positioning screws using intraoperative 3D imaging (by O-arm or motorized 3D C-arm) at our trauma center between 2022 and 2024. All 3D reconstructions were performed after reductions and temporary fixation appeared satisfactory on fluoroscopy. Reduction of the fibula in the notch was subjectively assessed by the operating surgeon. The primary outcome was the frequency and nature of immediate intraoperative revisions following 3D imaging. Early complications were noted. Results: About 22 patients (mean age 40) were included: 9 with proximal fibular fractures (AO type 44-C3), 11 with 44-C1 or 44-C2 fractures, 1 with a 44-B3 fracture, and 1 with an isolated posterior malleolar fracture. In 14 cases, two syndesmotic screws were used; in eight cases, only one was used. Although fluoroscopic findings appeared satisfactory, intraoperative 3D imaging prompted revision of syndesmotic reduction in nine cases (41%). Complications occurred in three cases: (1) deep venous thrombosis, (2) infection after an open fracture, and (3) secondary dislocation due to screw failure. Conclusion: Syndesmotic malreductions after trans-syndesmotic fib–tib screw stabilization are common and often missed on standard fluoroscopy. Intraoperative 3D imaging or postoperative CT is recommended to detect and address these malreductions in all syndesmotic injuries. Level of evidence: Level IV.